Septum Pellucidum Cyst in Patient with Parkinson’s Disease-minimally Invasive Staged Therapy - Ghallab, K.; Novák, Z.; Chrastina, J.; Baláž, M.; Říha, I. (Thamar University Journal of Natural & Applied Sciences, 2023)
Background: The aim of the case report is to present the minimally invasive staged treatment of a patient with motor complications of Parkinson’s disease with a large septum pellucidum cyst.Material and Method: A two-stage surgical strategy was proposed by the movement disorders team: neuroendoscopic cyst fenestration with subsequent implantation of deep brain stimulation electrodes (subthalamic nucleus) depending on the effect of neuroendoscopic treatment.Results: Despite the technical success of a neuroendoscopic cyst fenestration, as evidenced by a reduction in cyst volume, intraoperative ventriculocystography and postoperative CT showing free communication between the cyst and the ventricular system the motor symptoms caused by Parkinson’s disease remained unchanged. A bilateral subthalamic deep brain stimulation system was implanted with good functional results as documented by her UPRDS III score in the off-medication state (52 points preoperative and 34 point after 6 years postoperative) and reduction of L-DOPA equivalent dose (60% of the pre-deep brain stimulation level). Conclusion: Minimally invasive therapy-neuroendoscopic cyst fenestration, followed by a bilateral subthalamic stimulation implantation-led to the substantial and lasting improvement of the patient’s symptoms.